ON SOME SEMINORMED SEQUENCE SPACES DEFINED BY A MODULUS FUNCTION - Altin, Yavuz; Altinok, Hifsi; Colak, Rifat (Univ Kragujevac, Fac Science, 2006)
In this paper we define the space BV sigma (p, f, q, s) on a seininorrned complex linear space, by using modulus function. We give various properties and some inclusion relations on this spsce. Furthermore, we construct the sequence space BV sigma (p, f(k), q, s) and we give properties and some inclusion relations on this space.
Keywords: seminormed sequence spaces; seminormed complex linear space